2012
DOI: 10.1111/1365-2664.12012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mesofilter as a novel operational scale in conservation planning

Abstract: Summary1. Increased emphasis is being placed on developing effective biodiversity conservation tools for practical conservation planning. The mesofilter is such a biodiversity planning tool, but has yet to be fully explored to appreciate its effectiveness. The key premise of the mesofilter is that ecosystems contain certain physical elements that are specifically associated with a diversity of species. Identifying such mesofilters could therefore complement existing conservation planning tools such as coarse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…Yet, Crous et al . () found that percentage surface rock cover per se does not significantly structure grasshopper community composition in Afro‐montane grasslands. And so we hypothesised here that there may be confounding factors which could describe the observed grasshopper‐rockiness phenomenon.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Yet, Crous et al . () found that percentage surface rock cover per se does not significantly structure grasshopper community composition in Afro‐montane grasslands. And so we hypothesised here that there may be confounding factors which could describe the observed grasshopper‐rockiness phenomenon.…”
Section: Discussionmentioning
confidence: 97%
“…This could help explain the higher species richness in higher rocky grassland sites, as observed by Crous et al . (). Lower vegetation density, a correlate of higher percentage surface rock cover, can therefore predict the presence/absence of both certain grasshopper species individually, and certain grasshopper taxonomic groups across the landscape.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At a landscape scale, this emphasizes the importance of particular natural landscape features containing special niches to maximize overall biodiversity (Crous et al. ). The grazed sites had higher acoustic diversity than either the managed sites or grassy margins.…”
Section: Discussionmentioning
confidence: 99%